2018
DOI: 10.1111/jvim.15323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electroencephalographic findings with hippocampal magnetic resonance imaging volumetry in dogs with idiopathic epilepsy

Abstract: Background: In humans, temporal lobe epilepsy (TLE), is a type of focal epilepsy occurring mainly in the mesial TLE (mTLE), commonly associated with hippocampal sclerosis (HS). Objectives: According to recent studies, TLE might also occur in dogs and could be associated with hippocampal atrophy (HA)/HS. To date, hippocampal lesions have not been correlated with electroencephalographic (EEG) findings in epileptic dogs. Animals: An EEG examination, brain magnetic resonance imaging, and volumetric assessment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…However, the fact that other studies documented functional or structural changes of the hippocampus (10,12,13,28) warrants further investigations limited to hippocampus formation using H1-MRS. Further detailed classification of dogs with focal seizures and focal seizures evolving to generalized seizures, as well as use of continuous long-term electroencephalography, should be considered in order to improve anatomical localization of epileptic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fact that other studies documented functional or structural changes of the hippocampus (10,12,13,28) warrants further investigations limited to hippocampus formation using H1-MRS. Further detailed classification of dogs with focal seizures and focal seizures evolving to generalized seizures, as well as use of continuous long-term electroencephalography, should be considered in order to improve anatomical localization of epileptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the diagnosis of canine idiopathic epilepsy (IE) is made without evidence of MRI structural or morphological lesions or insults that secondarily influence the neuronal network (9). This concept might change in the face of growing evidence of documented structural changes in dogs with IE, like changes of apparent diffusion coefficient (ADC) parameters (10) or volumetric changes of white-to-gray matter ratio (11) or hippocampus (12,13). The main knowledge about generalized tonic-clonic seizures (GTCSs) is based on electrophysiological experiments that indicated involvement of bilateral cortical, subcortical, and brain stem networks in the seizure activity (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several quantitative MRI and functional neuroimaging techniques have been investigated in dogs with idiopathic/genetic epilepsy. Hippocampal atrophy (HA), similar to what is described in humans with mesial temporal lobe epilepsy (TLE) and hippocampal sclerosis, has been identified in up to 56 % of epileptic dogs in which volumetric MRI analyses are performed ( Czerwick et al, 2018 ; Etsey et al, 2017 ). Studies that have obtained contemporaneous EEG on dogs with HA have also demonstrated that epileptiform discharges frequently localize to the hemisphere containing the HA ( Czerwick et al, 2018 ).…”
Section: Spontaneous Neurological Diseases In Companion Animalsmentioning
confidence: 94%
“…El EEG muestra la función de la corteza cerebral y puede ser útil para determinar el diagnóstico de epilepsia y definir el tipo de trastorno convulsivo y la zona epileptogénica (14). Las ondas en punta, puntas en espiga, constituyen uno de los elementos patológicos más significativos del EEG.…”
Section: Tratamiento Para Los Tres Casosunclassified